Development of a prototype pet litter sand filtering machine / Muhammad Haziq Haikal Adli Rahimi and Norhisyam Jenal - Adli Rahimi, Muhammad Haziq Haikal; Jenal, Norhisyam (School of Mechanical Engineering, 2023)
Nowadays there are many veterinary clinics and animal hotels that provide care for pets and other animals. One of the important aspects that need to be maintained is the cleanliness of the pet and its surroundings. The pet litter station for example needs to be cleaned from time to time by separating solid faces from the sand by scooping manually using a shovel. To assist in this process, a Pet Litter Sand Filtering Machine is developed. The objective of this product is to develop a semi-automated pet litter sand filtering machine. This product works through a crank mechanism that connects the rod to the filter and is driven by an adapter and speed regulator circuit which controls the speed. The product is also movable because it is attached to wheels. This product is targeted at pet owners, veterinaries, and clinics because it is easy to use and helps clean pet litter in a faster and more convenient way